2017
DOI: 10.1248/bpb.b17-00463
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rh2 Inhibited Proliferation by Inducing ROS Mediated ER Stress Dependent Apoptosis in Lung Cancer Cells

Abstract: Key words ginsenoside Rh2; lung cancer; apoptosis; reactive oxygen species; endoplasmic reticulum stress Followed by serial biological steps including hyperplasia, metaplasia, dysplasia and in situ carcinoma, similar to other cancers, lung cancer eventually develops its malignancy marked by strong proliferative capacity which is characterized by resistance to apoptosis. 1) Nowadays, lung cancer is still among the top common cancers worldwide. According to the records, lung cancer composes 12.7% of cancer and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 27 publications
0
29
0
Order By: Relevance
“…Reactive oxygen species contribute to ER stress, a process called ROS-mediated ER stress. When mitochondrial dysfunction occurs, increased ROS production results in unfolded protein response in the ER, thus inducing ER stress, which if sustained, can lead to apoptosis [ 39 , 40 ]. Iwasawa et al suggested that when mitochondrial dysfunction occurs, the mitochondrial fission protein, fission 1 homologue (Fis1), serves to transmit an apoptotic signal from the mitochondria to the ER by interacting with Bap31 at the ER [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Reactive oxygen species contribute to ER stress, a process called ROS-mediated ER stress. When mitochondrial dysfunction occurs, increased ROS production results in unfolded protein response in the ER, thus inducing ER stress, which if sustained, can lead to apoptosis [ 39 , 40 ]. Iwasawa et al suggested that when mitochondrial dysfunction occurs, the mitochondrial fission protein, fission 1 homologue (Fis1), serves to transmit an apoptotic signal from the mitochondria to the ER by interacting with Bap31 at the ER [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, during the later stages of cancer, ROS accumulation induces p53 expression, which in turn causes cell cycle arrest at the G2/M phase, DNA fragmentation and apoptosis ( 38 ). It has been reported that G may induce cell cycle arrest or cell death by increasing ROS release in cancer cells ( 39 , 40 ). ROS has also been reported to be a mediator of ERK-induced cell death ( 41 , 42 ); specifically, elevated ROS results in sustained ERK activity, which in turn causes enhanced p53 expression ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ginsenoside Rg3 can also modulate the tumor environment through inhibiting angiogenesis and enhancing anti-tumor immune responses [241]. Moreover, ginsenoside Rh2 exhibits anti-tumor activity in human NSCLC H1299 cells and H1299 xenograft mice, through the induction of ROS-mediated ER-stress-dependent apoptosis [242]. It also suppresses cell proliferation and migration, and induces cell cycle arrest in human hepatocellular carcinoma HepG2 and Hep3B cells, and inhibits tumor growth in HepG2 xenograft mice [243].…”
Section: Ginsenosidesmentioning
confidence: 99%